Domestication of Temperate and Coastal Hybrids with Distinct Ancestral Gene Selection in Octoploid Strawberry. Issue 3 (1st November 2018) - Hardigan, Michael A.; Poorten, Thomas J.; Acharya, Charlotte B.; Cole, Glenn S.; Hummer, Kim E.; Bassil, Nahla; Edger, Patrick P.; Knapp, Steven J.
Abstract : Garden strawberry ( Fragaria × ananassa Duchesne ex Rozier) arose from spontaneous hybridization of distinct octoploid species 300 yr ago. Since its discovery in the 1700s, migration and selection restructured the genetic diversity of early hybrids to produce elite fruit‐bearing groups. Breeders' understanding of the genetic architecture of domesticated populations is incomplete. To resolve the impacts of domestication on strawberry genetic diversity, we analyzed genome‐wide DNA profiles of 1300 octoploid individuals (1814–present), including wild species, historic varieties, and the University of California germplasm collection. Commercially important California genotypes, adapted to mild coastal climates and accounting for a large fraction of global production, have diverged from temperate cultivars originating in eastern North America and Europe. Whereas temperate cultivars were shown to have selected North American Fragaria virginiana Miller ssp. virginiana ancestral diversity at higher frequencies, coastal breeding increased selection of Fragaria chiloensis (L.) Miller (beach strawberry) alleles in F . × ananassa, in addition to photoperiod‐insensitive flowering alleles from nonancestral F. virginiana (S.Watson) Staudt ssp. glauca, underscoring the role of continued adaptive introgressions in the domestication of artificial hybrids. Selection for mass production traits in coastal climates over the last 20 to 30 yr has restructured domesticated strawberry diversity on a scale similar to the first 200 yr of breeding; coastal F . × ananassa has diverged further from temperate F . × ananassa than the latter from their wild progenitors. Selection signatures indicate that strawberry domestication targeted genes regulating hormone‐mediated fruit expansion, providing a blueprint for genetic factors underlying elite phenotypes.